The Ukraine - Chapeye, Artem (Seven Stories Press, 2024)
"The Ukraine is a collection of 26 pieces that deliberately blur the line between nonfiction and fiction, conjuring the essence of a beloved country through its tastes, smells, and sounds, its small towns and big cities, its people and their compassion and indifference, simplicities and complications. In the title story, Chapeye facetiously plays with the English misuse of the article "the" in reference to Ukraine, capturing a country as perceived from the outside, by foreigners. That pseudo-kitsch, often historically shallow, and not-quite-real Ukraine resonates because of its highly engaging and brutally candid snapshots of ordinary lives and typical places. In "One Soul per Home" an elderly woman laments that the men are dying and the young are leaving for the cities, changing the face of her small town. In "The Unscrupulous Spirit of the Provinces," a couple of unspecified gender get stoned and go to church, and in "False Premises," a man romanticizes his younger years working for a Soviet fishing fleet only to reconstruct his nostalgia in the face of Putin's Russia. The Ukraine conveys to readers a place that Chapeye and his countrymen are currently fighting for with their lives. The book will feature a preface by the author, which he is writing on his phone from the front lines"--